2013
DOI: 10.1002/minf.201300004
|View full text |Cite
|
Sign up to set email alerts
|

Information Theory and Voting Based Consensus Clustering for Combining Multiple Clusterings of Chemical Structures

Abstract: Many consensus clustering methods have been applied in different areas such as pattern recognition, machine learning, information theory and bioinformatics. However, few methods have been used for chemical compounds clustering. In this paper, an information theory and voting based algorithm (Adaptive Cumulative Voting-based Aggregation Algorithm A-CVAA) was examined for combining multiple clusterings of chemical structures. The effectiveness of clusterings was evaluated based on the ability of the clustering m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 34 publications
(45 reference statements)
0
7
0
Order By: Relevance
“…The key information of interest is often obscured behind redundancy and noise, and grouping the data into clusters with similar features is one way of efficiently summarizing the data for further analysis [ 1 ]. Cluster analysis has been used in many fields [ 1 , 2 ], such as information retrieval [ 3 ], social media analysis [ 4 ], neuroscience [ 5 ], image processing [ 6 ], text analysis [ 7 ] and bioinformatics [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…The key information of interest is often obscured behind redundancy and noise, and grouping the data into clusters with similar features is one way of efficiently summarizing the data for further analysis [ 1 ]. Cluster analysis has been used in many fields [ 1 , 2 ], such as information retrieval [ 3 ], social media analysis [ 4 ], neuroscience [ 5 ], image processing [ 6 ], text analysis [ 7 ] and bioinformatics [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although the CVAA can outperform Ward’s method and give better results than other consensus clusterings, as shown by Saeed et al, different results are obtained every time the CVAA is applied because the final partition depends on the arrangement of partitions during the relabeling process. Therefore, the adaptive cumulative voting-based aggregation algorithm (A-CVAA) was used to overcome this limitation …”
Section: Methodsmentioning
confidence: 99%
“…Moreover, Saeed et al 25 used a cumulative voting-based aggregation algorithm (CVAA) for combining multiple clusterings of chemical structures and found that it could significantly improve the quality of clustering. In addition, an adaptive voting-based consensus method was used by Saeed et al 26 to obtain a final consensus partition with a greater quantity of mutual information associated with its clusters. However, an enhanced votingbased consensus method was introduced in this paper and compared with other consensus clustering methods (four coassociation-based, two graph-based, and two voting-based methods) and to the Ward's method to study the effectiveness of consensus methods for combining multiple clusterings of chemical structures.…”
Section: Introductionmentioning
confidence: 99%
“…Clustering analysis aims to detect the nature groups or clusters of data objects in attributes space, and it is one of the most important techniques in data mining [1], [2]. Clustering algorithms are used in a wide range of fields such as social media analysis [3], information retrieval [4], [5], image analysis [6], privacy preserving [7], text analysis [8], and bioinformatics [9], [10]. The goal of clustering is to group data objects into clusters such that the data objects in the same cluster are as similar as possible and the ones from different clusters are as dissimilar as possible [11].…”
Section: Introductionmentioning
confidence: 99%